Representasi Ilmiah dan Moral Anjing dalam Al-Qur’an: Analisis Tafsir Saintifik QS. Al-Kahfi: 18 dan QS. Al-A‘raf: 176 - Helda Pauziah; Serlyana Yuriska; Akhmad Dasuki (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study is motivated by the tendency of previous research on dogs in the Qur’an to focus primarily on legal aspects and negative perceptions, thus not fully exploring their broader representational dimensions; therefore, this study aims to analyze the scientific and moral representations of dogs in QS. Al-Kahf [18]: 18 and QS. Al-A‘raf [7]: 176 through a scientific exegesis approach. This research employs a qualitative library-based method with a descriptive-analytical approach, integrating classical and contemporary interpretations with modern scientific findings, particularly in animal biology. The findings reveal that dogs are represented in a complex manner through two main dimensions: as loyal and protective creatures in QS. Al-Kahf [18]: 18, and as a moral symbol for humans who follow their desires in QS. Al-A‘raf [7]: 176; furthermore, the Qur’anic description of dogs panting aligns with the biological mechanism of thermoregulation. In conclusion, the representation of dogs in the Qur’an is integrative, encompassing both biological and ethical dimensions, and opens a dialogical space between revelation and science in a contextual framework.